Stages of Using Crossword Puzzle Game Learning Media Assisted By Wordwall Application On Folklore Material in High School - Pramesti, Impala Agus; Huda, Miftakhul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to outline the step‑by‑step process for utilizing a crossword‑puzzle game as interactive learning media, leveraging the Wordwall application to enhance student engagement and achieve more focused, meaningful instruction. Methodology: Employing a qualitative design, researchers observed thirty‑five tenth‑grade students at SMA Muhammadiyah 1 Surakarta as they navigated the Wordwall platform to access and complete a crossword‑puzzle activity. Data were gathered through non‑numeric observations—focusing on students’ ability to follow each stage of the process—and were then analyzed and interpreted to assess usability and engagement. Results: All thirty‑five students successfully followed the prescribed stages (logging in, selecting the crossword puzzle, completing clues, and submitting answers) and reported finding the activity clear and enjoyable. Their performance and feedback indicated that the Wordwall crossword‑puzzle game was both accessible and motivating, leading to high levels of participation and satisfaction. Applications/Originality/Value: By detailing a replicable implementation framework for a gamified crossword activity, this study provides educators with practical guidance on integrating technology‑rich quizzes into the classroom. It demonstrates Wordwall’s potential as a feasible, fun learning medium that aligns with the technological literacy of today’s students, helping teachers design innovative lessons that sustain focus and meet learning objectives.